Pharmacological activities of chemically characterized essential oils from Haplophyllum tuberculatum (Forssk.) - Agour, Abdelkrim; Mssillou, Ibrahim; Allali, Aimad; Chebaibi, Mohamed; El Abdali, Youness; El Barnossi, Azeddin; Bin Jardan, Yousef A.; Wondmie, Gezahign Fentahun; Nafidi, Hiba-Allah; Bourhia, Mohammed; Bari, Amina; Lyoussi, Badiaa; et al. (Frontiers in Chemistry, 2023)
The present work aimed at characterizing the phytochemical composition of Haplophyllum tuberculatum essential oil (HTEO), assessing its antifungal activity against various fungal strains, evaluating its insecticidal and repulsive properties against Callosobruchus maculatus, and determine its antioxidant capacity. To this end, Gas chromatography-mass spectrometry analysis detected 34 compounds in HTEO, with β-Caryophyllene being the major constituent (36.94%). HTEO demonstrated predominantly modest antifungal effects, however, it sustains notable activity, particularly against Aspergillus flavus, with an inhibition rate of 76.50±0.60%. Minimum inhibitory concentrations ranged from 20.53±5.08 to 76.26±5.08 mg/mL, effectively inhibiting fungal growth. Furthermore, the antifungal, and antioxidant activities of HTEO were evaluated in silico against the proteins Aspergillus flavus FAD glucose dehydrogenase, and beta-1,4endoglucanase from Aspergillus niger, NAD(P)H Oxidase. Moreover, HTEO displayed strong insecticidal activity against C. maculatus, with contact and inhalation tests yielding LC50 values of 30.66 and 40.28 μL/100g, respectively, after 24 hours of exposure. A dose of 5 μL/100g significantly reduced oviposition (48.85%) and inhibited emergence (45.15%) compared to the control group. Additionally, HTEO exhibited a high total antioxidant capacity of 758.34 mg AAE/g EO, highlighting its antioxidant potential. Insilico results showed that the antifungal activity of HTEO is mostly attributed to γ-Cadinene and p-Cymen-7-ol, while antioxidant is attributed to α-Terpinyl isobutyrate displayed. Overall, HTEO offers a sustainable and environmentally friendly alternative to synthetic products used to manage diseases